2023
DOI: 10.3390/ijms24087534
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cultured Rat Hepatocytes Using RNA-Seq In Vitro

Abstract: Compared to other techniques, RNA sequencing (RNA-Seq) has the advantage of having details of the expression abundance of all transcripts in a single run. In this study, we used RNA-Seq to monitor the maturity and dynamic characteristics of in vitro hepatocyte cultures. Hepatocytes, including mature hepatocytes and small hepatocytes, were analyzed in vitro using RNA-Seq and quantitative polymerase chain reaction (qPCR). The results demonstrated that the gene expression profiles measured by RNA-Seq showed a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[61] Finally, the preference for SHs in our study stems from their impressive proliferative capacity and their significant potential to differentiate into MHs. [21,28,62] Unlike MHs, which are considered the gold standard in vitro cell models but tend to undergo EMT within a short duration, hindering hepatocyte growth and function, even under favorable conditions, SHs offer a more sustainable model for evaluating long-term effects. [21] Lin et al demonstrated that SHs exhibit superior performance in ameliorating injured cell viability and inhibiting apoptosis/necrosis compared to MHs under specific concentrations of tannic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[61] Finally, the preference for SHs in our study stems from their impressive proliferative capacity and their significant potential to differentiate into MHs. [21,28,62] Unlike MHs, which are considered the gold standard in vitro cell models but tend to undergo EMT within a short duration, hindering hepatocyte growth and function, even under favorable conditions, SHs offer a more sustainable model for evaluating long-term effects. [21] Lin et al demonstrated that SHs exhibit superior performance in ameliorating injured cell viability and inhibiting apoptosis/necrosis compared to MHs under specific concentrations of tannic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from the cultured hepatocytes by using TRIzol. [27,28] The quality of the extracted RNA was assessed by determining the OD260/OD280 absorption ratio. Subsequently, total RNA (500 ng) was reverse-transcribed into single-stranded cDNA by using PrimeScript RTase and 50 pM random hexamer primers.…”
Section: Total Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated an inverse relationship between cell proliferation and differentiation [ 15 , 32 ]. In addition, SHs exhibited a superior ability to maintain 3D structures and resist differentiation into fibroblast-like cells compared with MHs [ 22 ]. Therefore, we hypothesize that the stimulation of APAP-SHs following TA supplementation led to advanced differentiation, resulting in the formation of more functionally mature liver tissue during in vitro proliferation ( Figure 3 F).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to assess short-term effects, we utilized primary mature hepatocytes (MHs), the gold standard in vitro cell model, because they can retain their functionality over short durations [ 21 ]. To evaluate long-term effects, we used small hepatocytes (SHs), known for their remarkable ability to proliferate and high potential to differentiate into MHs [ 22 ]. This study investigated the hepatoprotective and hepatocurative effects of TA through comprehensive in vitro and in vivo analyses.…”
Section: Introductionmentioning
confidence: 99%